Farm accidents in children. Issue 6844 (4th July 1992) - Cameron, D.; Bishop, C.; Sibert, J. R.
Abstract : OBJECTIVE--To examine the problem of accidental injury to children on farms. DESIGN--Prospective county based study of children presenting to accident and emergency departments over 12 months with injuries sustained in a farm setting and nationwide review of fatal childhood farm accidents over the four years April 1986 to March 1990. SETTING--Accident and emergency departments in Aberystwyth, Carmarthen, Haverfordwest, and Llanelli and fatal accidents in England, Scotland, and Wales notified to the Health and Safety Executive register. SUBJECTS--Children aged under 16. MAIN OUTCOME MEASURE--Death or injury after farm related accidents. RESULTS--65 accidents were recorded, including 18 fractures. Nine accidents necessitated admission to hospital for a mean of two (range one to four) days. 13 incidents were related to tractors and other machinery; 24 were due to falls. None of these incidents were reported under the statutory notification scheme. 33 deaths were notified, eight related to tractors and allied machinery and 10 related to falling objects. CONCLUSIONS--Although safety is improving, the farm remains a dangerous environment for children. Enforcement of existing safety legislation with significant penalties and targeting of safety education will help reduce accident rates further.